Factorial Design-Based Nanocarrier Mediated Formulation of Efavirenz and Its Characterization - Chawla R.; Karri V.; Rani V.; Mishra M.; Kumar K. (My University, 2025)
Efavirenz (EFV) suffers from poor aqueous solubility which results in low bioavailability of the drug. Nanocarrier-based drug delivery systems offer a suitable alternative for improving the physico-chemical properties of the drug and hence its efficacy. Nanosuspension (NS) of EFV was formulated by solvent-anti solvent precipitation method using PVP K-30 as stabilizer and sodium lauryl sulphate (SLS) as the wetting agent. Multi-level factorial design was applied to select the optimal formulation which was further characterized. The optimal batch exhibited mean particle size of 305nm and polydispersity index (PDI) of 0.345. Solid-state characterization studies of the NS conducted using scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction, and differential scanning calorimetry (DSC) revealed compatibility between the drug and the excipients and modest alteration in the crystallinity of the drug. There was progressive increase in the solubility of the drug when incorporated in NS from 17.39μg/ml to 256μg/ml. Further, drug release studies showed significantly better and controlled drug release pattern in comparison to the free drug due to the presence of nanosized particles in the formulation. © 2022 World Scientific Publishing Company.